Development of asymmetric carbon hollow fiber membrane for gas separation - Mustafa, Azeman; Aziz, Madzlan; Ismail, Ahmad Fauzi; Hasbullah, Hasrinah; Sanip, Suhaila; Ng, Be Cheer; Hassan, Abdul Rahman (Universiti Teknologi Malaysia, 2006)
The objective of this research is to develop a novel asymmetric carbon hollow fiber membrane and to characterize it’s gas separation performance and morphology. Polyacrylonitrile (PAN) was chosen as the precursor for carbon membranes. The hollow fiber membranes were produced using the dry/wet spinning process. PAN hollow fiber membranes were converted to carbon hollow fiber membranes with inert gas pyrolysis process. Carbon hollow fiber membranes were characterized by pure gas permeation measurement, Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR) and Thermogravimetry Analysis (TGA). The influence of the pyrolysis conditions on carbon membrane performance was investigated. Pyrolysis parameters including pyrolysis temperature, heating duration (soak time) and purge gas flow rate were studied. The results showed that pyrolysis temperatures of 700 oC to 800 oC O2/N2 selectivity from 1.1 to 1.85 and the maximum permeability O2 was increased achieved at 600 oC with 480 GPU. Although the selectivity of 3.1 was achieved at 250 oC, the membrane was not a pure carbon membrane. Longer duration of heating improved the selectivity from 1.1 to 1.8 with an increased in permeability at the initial stage. A decreased in permeability occurred at 180 min heating duration. Carbonized membrane with 10 min heating duration exhibited high selectivity of 3.7 with poorer permeability compared to PAN membranes. However, high purge gas flowrate gave an increase for O2 and N2 permeability from the original 50 – 130 GPU to 150 – 730 GPU without influencing its selectivity. Therefore, pyrolysis condition has pronounced influence on asymmetric carbon hollow fiber membranes for gas separation.